CD20 antibodies in the targeting of B-cell malignancies and autoimmunity - Tedder, Thomas (Henry Stewart Talks, 2007)
Antibody targeting of B-cell malignancies and autoimmunity, CD20 antibody immunotherapy, CD20 structure and function, Antibody-dependent cellular cytotoxicity, Complement-dependent cytotoxicity, Mouse models of CD20 immunotherapy, Lymphoma immunotherapy, Immunotherapy for autoimmunity
Archived at 2019/06/13